“Out of the Frying Pan, Into the Fire”: An Interview with Laura Hird - Botamino González, Clara (Complutense Journal of English Studies, 2021)
Full of morbid humour and painfully honest narrations, Laura Hird’s stories— mainly set in the city of Edinburgh— deal with relationships of power, family values and her narratives always offer her unique view on the city she was born in and its people. Through these stories, she presents her unparalleled perspective on the beauty of some of the city’s hidden locations which are not portrayed by others. As she mentions in Dear Laura, Hird considers herself to be a ‘constipated romantic’, and that is simply a great way to summarise her work, as her way of portraying life through writing is not always pleasant, yet ever phenomenal. While her first published work allowed her to be included amongst a group of male authors; her first story collection and her novel roared originality and offered a different city of Edinburgh, and her last collection put the cherry on top with yet more uncomfortably true stories about queer Scottishness as part of her urban observations.